PENGARUH NON PERFORMING FINANCING DAN OPERATIONAL EFFICIENCY RATIO TERHADAP KINERJA KEUANGAN (Studi Empiris pada Bank Umum Syariah tahun 2016-2018) - Isnaeni, Wina Ayu; Romadona, Trina; Wahyuni, Sri (Kompartemen : Jurnal Ilmiah Akuntansi, 2021)
This study aims to examine empirically the effect of Non Performing Financing (NPF) and Operational Efficiency Ratio (OER) on financial performance. Financial performance is measured using Return on Assets (ROA). The population used in this study is Islamic Commercial Banks registered with the Otoritas Jasa Keuangan. Sampling using purposive sampling method. Secondary data is in the form of annual financial reports published in 2016-2018. The data analysis technique used is multiple regression analysis. The results showed that NPF has a negative effect on financial performance while OER has a positive effect on financial performance.